Pediatric dentistry sealants, do they really protect teeth from different mechanical processes?" Literature review - Vasallo Chavez, Fiorella (2021)
The use of pit and fissure sealants in the area of pediatric dentistry has been very helpful as a preventive measure to avoid carious lesions generally given in the occlusal area of the first permanent molars erupted. These sealants have had constant variations over time, however, the most used are resinous sealants. These types of sealants are mainly classified in polymerization, viscosity and translucency. As dentistry has advanced, they have been divided into two groups (hydrophobic and hydrophilic), both with different characteristics, but with the same purpose, to provide a protective barrier between extrinsic factors and the tooth. However, when in contact with different elements such as humidity, carbohydrates and saliva, as well as having a bad application on the pits and fissures, these tend to fail and begin to present diverse problems such as microfiltration, retention failures and their microhardness. The objective of this literature review was to recognize whether these sealants are adequate to protect the teeth from external factors and whether they can resist various mechanical changes. For this purpose, a literature review was carried out in various databases and dental journals, and articles were selected according to their evidence, established criteria and the year of publication, which was between 2015 and 2020.